CAR-T cell potency: from structural elements to vector backbone components - Marzieh Mazinani; Fatemeh Rahbarizadeh (BMC, 2022)
Abstract Chimeric antigen receptor (CAR) T cell therapy, in which a patient's own T lymphocytes are engineered to recognize and kill cancer cells, has achieved remarkable success in some hematological malignancies in preclinical and clinical trials, resulting in six FDA-approved CAR-T products currently available in the market. Once equipped with a CAR construct, T cells act as living drugs and recognize and eliminate the target tumor cells in an MHC-independent manner. In this review, we first described all structural modular of CAR in detail, focusing on more recent findings. We then pointed out behind-the-scene elements contributing to CAR expression and reviewed how CAR expression can be drastically affected by the elements embedded in the viral vector backbone.